Postsynthetic acetylation of histones during the cell cycle: a general function for the displacement of histones during chromatin rearrangements. - Loidl, P (1987)
Postsynthetic acetylation of core histones exhibits a peak during S-phase of the Physarum cell cycle. The maximum 3H-acetate incorporation precedes the maximum of histone synthesis. Acetate is incorporated into all core histones during S-phase, but only into H2A and H2B during G2-period. Resolution of acetylated H4-subspecies reveals acetate incorporation into preexisting H4, but not into newly synthesized molecules during mitosis and early S-phase. In a protamine competition assay histones from S-phase chromatin are released at lower protamine concentrations as compared to the lower acetylated G2-chromatin. We demonstrate a preferential release of highly acetylated H4-subspecies at low protamine concentrations. Our results fit into a general model of the relationship between histone acetylation and chromatin assembly. According to this model acetylation of core histones would serve as a signal for displacement of histones from nucleosomes by modulating histone-protein or histone-DNA interactions. We propose that this mechanism operates during DNA-replication and transcription, as well as during other chromatin rearrangements.